2019
DOI: 10.3390/cancers11081047
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Visual Outcomes for Small Uveal Melanoma Staged T1 Treated by Proton Beam Radiotherapy

Abstract: There is increasing evidence of the survival benefit of treating uveal melanoma in an early stage, however it is important to discuss with the patient the associated risk of visual loss. We investigated visual outcomes for uveal melanomas staged T1 (T1UM) treated by proton beam radiotherapy (PBR) as a function of their distance to fovea-optic disc. This retrospective study included a cohort of 424 patients with T1UM treated with PBR between 1991 and 2010 with at least a 5-year follow-up. Visual acuity (VA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For these reasons, an understanding of long-term visual outcomes and their associations with radiation treatment planning parameters are critical for optimal care of choroidal melanoma patients. There have been several reports on visual outcomes after radiation therapy, as well as on factors associated with visual outcomes [14,[17][18][19]. It is well known that tumor height and distance of the tumor from the optic disc or fovea are commonly associated with the final VA [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, an understanding of long-term visual outcomes and their associations with radiation treatment planning parameters are critical for optimal care of choroidal melanoma patients. There have been several reports on visual outcomes after radiation therapy, as well as on factors associated with visual outcomes [14,[17][18][19]. It is well known that tumor height and distance of the tumor from the optic disc or fovea are commonly associated with the final VA [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on visual outcomes after radiation therapy, as well as on factors associated with visual outcomes [ 14 , 17 19 ]. It is well known that tumor height and distance of the tumor from the optic disc or fovea are commonly associated with the final VA [ 18 20 ]. These studies had many patients, and long follow-up periods; therefore, they showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term clinical outcomes [25,[36][37][38][39] reported in the literature are based on the existing geometrical eye model [1] available in EYEPLAN and EOPP (Varian Medical Systems Particle Therapy GmbH & Co. KG, Troisdorf, Germany) software, which is less accurate than 3D delineations based on CT or MRI [14,17,40]. A translation to an expected reduction in complications is therefore difficult to make.…”
Section: Bed Comparison (Rbe-weighted Inmentioning
confidence: 99%
“…Some recent studies suggested that early treatment of UM may have a beneficial effect on survival (9)(10)(11). PBR could be of particular advantage, as the damaging side effects on vision caused by the destruction of non-malignant tissue surrounding the tumour seem to be less pronounced in small T1 tumours compared to other methods of radiotherapy (12). This could lower the threshold for early treatment of small tumours near the fovea and disc.…”
Section: Introductionmentioning
confidence: 99%